2009
DOI: 10.1038/sj.bjc.6605040
|View full text |Cite
|
Sign up to set email alerts
|

T-regulatory cell modulation: the future of cancer immunotherapy?

Abstract: T-regulatory cells suppress anti-tumour immunity in cancer patients and in murine tumour models. Furthermore, their activity is likely to have an effect on the effectiveness of immunotherapeutic treatments for cancer. Here we describe the current status of developing clinical strategies for modulating Treg activity in cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
68
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(69 citation statements)
references
References 51 publications
1
68
0
Order By: Relevance
“…Once we found that OX40 and CTLA-4 were highly expressed by tumor-specific Tregs at the tumor site, we decided erance (21) and to a worse prognosis (6,22) and probably explain many failures of cancer immunotherapy (4,23,24). Therefore, Tregs are now identified as a new target in the host that could be neutralized to reverse the suppressive effects of the tumor on the immune system (5,25,26). Tregs are usually identified by their expression of FOXP3.…”
Section: Discussionmentioning
confidence: 99%
“…Once we found that OX40 and CTLA-4 were highly expressed by tumor-specific Tregs at the tumor site, we decided erance (21) and to a worse prognosis (6,22) and probably explain many failures of cancer immunotherapy (4,23,24). Therefore, Tregs are now identified as a new target in the host that could be neutralized to reverse the suppressive effects of the tumor on the immune system (5,25,26). Tregs are usually identified by their expression of FOXP3.…”
Section: Discussionmentioning
confidence: 99%
“…A commonly used chemotherapeutic agent CY can selectively deplete Treg cells when administered more frequenty or "metronomically" at a dose substantially lower than the maximum tolerated dose. Such low-dose CY is not only immunostimulatory but also avoids CY high-dose toxicity (16,42). In addition, the restoration of Treg numbers and function 10 days after low-dose CY administration implies that a limited period of Treg cell inhibition may avoid potential autoimmunity (15).…”
Section: Discussionmentioning
confidence: 99%
“…Immunotherapy for patients with colorectal cancer represents a realistic alternative approach to treatment of this disease [62][63][64] . The last 20 years has seen a wide range of publications on tumor immunity and the prognostic impact of immune and inflammatory cell types in the microenvironment of colorectal tumors demonstrating promising results both in vitro and in vivo.…”
Section: The Invasive Front Of Colorectal Cancer: Anti-tumor Factorsmentioning
confidence: 99%